2015
DOI: 10.1137/140960967
|View full text |Cite
|
Sign up to set email alerts
|

A Spectral Characterization of Controllability for Linear Discrete-Time Systems with Conic Constraints

Abstract: In this paper, we generalize all previously known results on the controllability of discrete-time linear systems with conic input and/or state constraints. In addition, we single out two cases of the problem which did not appear in the literature before. We provide a characterization for the first one of these new cases. For the second newly introduced case, we show that it is rare and pathological. Moreover, we show that the classical results cannot be extended to this last pathological case. These results al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…where ℱ is a strict convex process. Indeed, it is well-known (see, e.g [28,31] that a result similar to (31) holds for (46): Let ℱ ∈ S(ℝ n , ℝ n ), then (46) is controllable ⟺ ℱ is reproducing and Im(ℱ − λI) = ℝ n ,…”
Section: Robustness Of Controllability Of Differential and Differencementioning
confidence: 82%
See 1 more Smart Citation
“…where ℱ is a strict convex process. Indeed, it is well-known (see, e.g [28,31] that a result similar to (31) holds for (46): Let ℱ ∈ S(ℝ n , ℝ n ), then (46) is controllable ⟺ ℱ is reproducing and Im(ℱ − λI) = ℝ n ,…”
Section: Robustness Of Controllability Of Differential and Differencementioning
confidence: 82%
“…In the case K = ℝ, a number of equivalent characterisations for controllability of inclusions (30) have been obtained in [1,5] (see also [28] for the case of discrete-time systems x k + 1 ∈ ℱ(x k ), k = 0, 1, …), one of which can be stated as follows (see Aubin et al [1]): Let ℱ ∈ S(ℝ n , ℝ n ), then (30) is controllable ⟺ ℱ is reproducing and Im(ℱ − λI) = ℝ n ,…”
Section: Robustness Of Controllability Of Differential and Differencementioning
confidence: 99%
“…We call L − and L + , respectively, the minimal and maximal linear processes associated with H. If H is not clear from context, we write L − (H) and L + (H) in order to avoid confusion. Example 2: Let H be of the form (6). It can be shown that if the set {u | Bu = 0, Du ∈ Y} is a subspace, then…”
Section: Convex Processesmentioning
confidence: 99%
“…This means that cl(H(K)) ⊆ K since K is closed. Hence, H(K) ⊆ K. In other words, K is strongly H invariant due to Lemma 3. There is a link between weakly H invariant cones and eigenvalues of the dual of H, given in [6,Thm. 3.2].…”
Section: H(k)mentioning
confidence: 99%
See 1 more Smart Citation